Legal Analysis of The Judge's Decision on The Criminal Act of Money Politics in the 2019 Elections in East Luwu (Study of Decision Number 61/Pid.Sus/2019/Pn.Mll): A Critical Discourse Analysis - Egi Ramdhani Syahriwijaya; Muammar Arafat Yusmad; Firman Muh. Arif (Universitas Islam Negeri Palopo, 2025)
This study examines the judicial discourse surrounding money politics in Indonesian electoral processes through a critical discourse analysis of Decision Number 61/PID.SUS/2019/PN.MLL from the Malili District Court regarding criminal acts of money politics during the 2019 elections in East Luwu Regency. Using Fairclough's three-dimensional framework of critical discourse analysis, this research investigates how legal language constructs and legitimizes judicial reasoning in electoral corruption cases, while examining the underlying power relations and ideological assumptions embedded within the court's decision. The methodology combines textual analysis, discursive practice examination, and sociocultural practice investigation to uncover how the judge's linguistic choices reflect broader institutional attitudes toward electoral integrity and democratic governance. The study analyzes lexical choices, syntactic structures, modality, and argumentation patterns within the legal text to reveal how judicial discourse shapes public understanding of electoral crimes and their consequences. Key findings reveal that the judicial discourse employs specific linguistic strategies that position money politics as a threat to democratic legitimacy while simultaneously reinforcing state authority in electoral oversight. The analysis demonstrates how legal language serves not merely as a neutral vehicle for justice delivery but as a powerful tool for constructing social reality and reinforcing existing power structures. The court's decision reflects tensions between legal formalism and contextual considerations of local political dynamics in East Luwu. The research contributes to understanding how judicial discourse in Indonesia's post-reform era constructs electoral integrity narratives and legitimizes legal interventions in political processes. It reveals the complex interplay between legal reasoning, political context, and social power relations in contemporary Indonesian democracy. The findings have implications for legal reform, judicial training, and broader discussions about combating electoral corruption in emerging democracies.